Pelatihan Penggunaan Alat Peraga untuk Mengkonstruksi Prinsip-Prinsip Dasar dalam Matematika Guru Sekolah Dasar Se-Kecamatan Kuantan Tengah Taluk Kuantan - Syofni Syofni; Sakur Sakur; Titi Solfitri; Nahor Murani Hutapea; Syarifah Nur Siregar (Jurnal Pengabdian Masyarakat (ABDIRA), 2022)
This community service activity (PKM) aims to rectify misconceptions and procedural abilities of elementary school teachers in constructing the operation properties of addition and subtraction of integers, formulas of two-dimentional figures and three-dimetional figures. This activity is in form of training in the use of teaching aids to construct the properties of addition and subtraction of integers, the formula for the area of a plane and the formula for the volume of geometric figures for elementary school teachers in Kuantan Tengah District, Taluk Kuantan. There were 25 elementary school teacher participants who participated in this training. The training was held from August 14, 2021 to August 28, 2021. The training was carried out in two ways, namely offline meetings on August 14, 2021, followed by assignments and online meetings on August 28, 2021 via zoom. The results of the activity showed a significant increase in the ability to construct the basic principles of mathematics by the trainee teachers.